2012
DOI: 10.1021/nn303546m
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Ordering of PTCDA Molecules: The Key Role of Dispersion Forces in an Unusual Transition from Physisorbed into Chemisorbed State

Abstract: Adsorption and self-assembly of large π-conjugated 3,4,9,10-perylene tetracarboxylic dianhydride (PTCDA) molecules on rutile TiO(2)(110) surface have been investigated using a combination of high-resolution scanning tunneling microscopy (STM), low-energy electron diffraction, and density functional theory calculations with inclusion of Grimme treatment of the dispersion forces (DFT-D). Evolution of the STM images as a function of PTCDA coverage is caused by transition of the adsorption mode from physisorbed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 62 publications
5
62
1
2
Order By: Relevance
“…6,7 Ahead of an impressive increase of the number of newly synthesized PTCDI derivatives for both OPVs 8 and OFETs, 9 the advanced modeling of perylenes is mostly focused on the intermolecular coupling geometry, 10 which affects the optical spectrum, 11 and on the structure of monolayer phases at surfaces. [12][13][14] From the experimental point of view, the spectroscopic characterization of the molecular orbitals of the free PTCDI molecule, as well as of perylene, is largely outdated or limited. [15][16][17][18] In this context, the knowledge of the molecular orbital symmetry and energy, as measured in NEXAFS, is fundamental to understand the key parameters that govern the performances of an archetypal device, such as the orientation of the molecules on the surfaces 19 and the mechanism of charge transfer to the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Ahead of an impressive increase of the number of newly synthesized PTCDI derivatives for both OPVs 8 and OFETs, 9 the advanced modeling of perylenes is mostly focused on the intermolecular coupling geometry, 10 which affects the optical spectrum, 11 and on the structure of monolayer phases at surfaces. [12][13][14] From the experimental point of view, the spectroscopic characterization of the molecular orbitals of the free PTCDI molecule, as well as of perylene, is largely outdated or limited. [15][16][17][18] In this context, the knowledge of the molecular orbital symmetry and energy, as measured in NEXAFS, is fundamental to understand the key parameters that govern the performances of an archetypal device, such as the orientation of the molecules on the surfaces 19 and the mechanism of charge transfer to the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46] In the second case, PTCDA molecules present a flat lying geometry on the surface. 43 Our calculations 18 for the two cases show different properties: while the tilted geometry has a weak interaction with the surface, the flat geometry develops a stronger one, with a significant molecular distortion. The interface energy level alignment is very sensitive to the adsorption geometry: the flat geometry presents a much larger interface dipole potential (1.7 eV) than the tilted case (0.3 eV), due to a larger charge transfer between the molecule and the oxide.…”
Section: Results For Different Organic Molecules (Ptcda Zn-tpp and Tmentioning
confidence: 85%
“…Recent works 42,43 have proposed two likely candidates for PTCDA adsorption on TiO 2 (110). In one case, PTCDA molecules are adsorbed on the oxide surface lying along one of their long sides in a tilted geometry, see Figure 2, in similarity to the cases of PTCDI, perylene or pentacene.…”
Section: Results For Different Organic Molecules (Ptcda Zn-tpp and Tmentioning
confidence: 99%
“…Additionally, ordering of the molecules in the layers is shown to vary from a slightly tilted geometry, to a disordered one, and to a nearly flat-lying geometry as the coverage density increases from the submonolayer to monolayer, and to multilayer regimes [29]. These results can be confronted with scanning tunnelling microscopy studies discussing the influence of dispersion forces on the supramolecular ordering of the molecules in a layer described by Godlewski et al [28]. These authors have shown that at a low coverage, below 0.7 ML, molecules form poorly ordered layers of physisorbed species.…”
Section: Reviewmentioning
confidence: 99%